Использование информационных технологий при организации outlet бизнеса - Гуца, О. Н.; Овсюченко, Ю. В.; Буцукина, И. Б. (ХНУРЭ, 2014)
OUTLET CENTER is a new, quickly developing form of trade enterprise. Features of OUTLET CENTER demand introduction of ERP system for successful management. For introduction of ERP it is necessary to describe and optimize business processes which are at the enterprise. Imitating modeling is the most important instrument of optimization of business processes. Introduction of ERP increases competitiveness of trade enterprise.
Keywords: организация OUTLET бизнеса; использование информационных технологий